EFEKTIVITAS METODE DEMONSTRASI DAN CERAMAH TERHADAP PERUBAHAN SIKAP REMAJA PUTERI TENTANG SADARI - Sumarah, Sumarah; Rokhaelisyah, Rokhaelisyah; Suherni, Suherni (Poltekkes Kemenkes Yogyakarta, 2014)
The incidence of breast cancer in Indonesia by 36 per 100,000 women, the data from the Hospital Information System (SIRS) in Indonesia in 2007 is known that breast cancer ranks first in-patients (16.85%) and outpatient (21.69%) it higher than that of cervical cancer(17%).Number of patients inDharmaisCancerHospital also continued to increase, in2003, therewere221 casesin2008, it has increase three times into 657 cases. Based on reports fromYogyakarta City Health Department in 2011, found as many as 545 cases.BSEis oneof themeasures ofearly detectionto find early stage breast cancerwhowould bemore effective if done as early as possible. While public awareness and knowledge about breast cancer and adolescents who perform 8SE correctly still low.Thepurpose of research to prove the effectiveness difference demonstration and lecturemethods to change the attitude of adolescent about BSE.Experimental researchmethods. Apopulation of 164 students. 35 samples were taken with the studentsnext to a simple random sampling technique. Analysis of the data using a paired t test. Results: The average value of attitudes about breast self- examination before being given counseling with the lecture method was 71.43 and after counseling is 74.37 with an average difference of 2.94 and a p-value 0.026, while the average value of attitudes about BSE before counseling by the method of demonstration was 73.48 and after counseling is 80.51with an average difference of 7.03 and a p-value of 0.000. These results can be concluded that the method is more effective in comparison demonstration lectures. Conclusion: There is a difference in the effectiveness of the counseling methodwith a lecture anddemonstration to change attitudes about adolescent BSE.